Data from: Molecular assessment of Pocillopora verrucosa (Scleractinia; Pocilloporidae) distribution along a depth gradient in Ludao, Taiwan - De Palmas, Stéphane; Soto, Derek; Ho, Ming Jay; Denis, Vianney; Chen, Chaolun Allen; Ho, Ming-Jay (Dryad, 2018)
It can be challenging to identify scleractinian corals from the genus
Pocillopora (Lamarck 1816) in the field because of their large range of
inter- and intra-specific morphological variation that co-occur with
changes in the physical environment. This task is made more arduous in the
context of a depth gradient, where light and water current could greatly
affect the morphology of the corallum. Pocillopora verrucosa (Ellis and
Solander, 1786) in Taiwan was previously reported exclusively from shallow
waters (<10m in depth), but a recent observation of this species in
the mesophotic zone (>40m in depth) questions this bathymetric
distribution. We used the mitochondrial open reading frame and the histone
3 molecular markers to investigate the vertical and horizontal spatial
distribution of P. verrucosa around Ludao (Green Island), Taiwan. We
genotyped 101 Pocillopora verrucosa-like colonies collected from 4 depth
zones, ranging from 7 to 45m, at 3 sites around the island. Of the 101
colonies sampled, 85 were genotyped as P. verrucosa, 15 as P. meandrina,
and one specimen as an undescribed Pocillopora species. P. verrucosa was
found at all depths, while P. meandrina and the undescribed Pocillopora
specimen were limited to 15m depth. P. verrucosa has a large bathymetric
distribution around Ludao and could benefit from the refuge that the
mesophotic zone offers. This study illustrates the difficulty of
identifying Pocillopora corals in the field and emphasizes the relevance
of molecular taxonomy as an important and complementary tool to
traditional taxonomy for clarifying vertical and horizontal species
distribution. Our results also illustrate the need in conservation biology
to target species genetic diversity rather than just species diversity.
Histone FASTA alignmentHistone 3 region alignment for all haplotype H1 to
H9mtORF FASTA alignment dataMitochondrial Open Reading Frame alignment
data for all samples
Keywords: molecular ecology; Coral taxonomy; Pocilloporids; Pocillopora meandrina; Deep Reef Refugia Hypothesis; Pocillopora sp.; Pocillopora verrucosa